Preservation of the Heritage of the Metabolism Architecture in Modern Japan - Palagina, Anastasia (project baikal, 2019)
The main focus of the article is on the problem of the modern attitude to the remaining legacy of Metabolism in Japan. In the course of the research rare cases of renovation of architecture in Japan were revealed. In order to determine the historical value of modern architecture in Japan, a system “language-tradition-space” which links with the Japanese culture, was used. The full-scale survey of one of the Tokyo districts was also carried out to prove the certain connection between the value of space and time in modern Japanese culture.
Keywords: modern Japanese architecture; Metabolism; restoration; renovation; cultural heritage; tradition